Nurse performance and the knock out polio 1997 in a Metro Manila health district - Sandalo, Maribel R. (2000)
The community health nurse's primary obligation is to provide health services to the populace. Her work deals with providing holistic and continuing health care that focuses on early diagnosis and treatment directed towards fostering a sense of responsibility among the people of the community.The community health nurse works closely with the physician. She acts as a manager, supervisor and coordinator to other health team members. This is probably the reason why she was given the task to lead the Department of Health's National Immunization Day/Knock Out Polio (NID/KOP) implementation from the preparatory, actual and evaluation phases. Considering other tasks and activities the community health nurse is expected to render at the health center, the nurse is burdened with the fact that the success of the immunization program depends on how she performs her role as its manager and supervisor.This study investigates if the success of the Knock Out Polio (KOP) is related to nurse performance. It also describes performance and extent of participation of the nurse in KOP activities. The study likewise investigates whether the factors related to KOP activities (manpower, support system, logistics and supplies and OPV posts) will enhance nurse performance resulting in high KOP coverage outcome.The study was conducted in the three (3) cities of District Health Office (DHO) IV (Las Pi?as, Muntinlupa and Para?aque). Fifty two (52) community health nurses assigned to the health centers of the aforementioned cities were the subjects of the study. They were observed during the three (3) phases of KOP activities - preparatory, actual and evaluation phases. Statistical treatment of the data utilized descriptive statistics, Pearson product moment correlation coefficient; ANOVA and T-test with the level of significance preset at =.05.The study yielded these major findings:1) The community health nurses' mean level of performance in carrying out each of the functions during KOP was interpreted to be outstanding. In all phases, nurse's performance rating was outstanding, but the nurses obtained highest performance during the actual and evaluation phases.2) There were only nine (9) health centers with high KOP coverage outcome. This can be attributed to the following factors: (a) saturation of small population size of the communities covered by the health centers; (b) presence of mobile health teams; and (c) presence of Oral Polio Vaccine (OPV) posts in accessible areas. On the other hand majority (83) of the health centers reported low coverage outcome due to the following reasons: (a) a number of health centers cover elite subdivisions; (b) some of the health centers are physically inaccessible; (c) inappropraite scheduling of immunization days; (d) lack of transportation allowance among health care workers in order to reach far-flung areas; and (e) high degree of saturation of target population since KOP is on its 4th year of implementation.3) The data did not show any significant relationship between nurse performance and KOP coverage outcome (p value = 0.204).
Therefore, KOP outcome cannot bet attributed solely on nurse performance. Probable reasons are as follows: a) KOP activities were carried out through team effort; b) tasks and functions of other members of the health team overlap or even duplicate with those of the nurse hence completion of nurses' tasks may have been done with the help of other involved on the KOP activity.4) Cities of Las Pi?as, Muntinlupa and Para?aque reported adequate to more than adequate factors necessary in achieving goals and targets of the KOP campaign. Among these were manpower, logistics and supplies such as OPV, cold packs, vaccine carrier and Patak Centers.5) There was no association between nurse performance and adequacy of factors, namely, manpower (p = .508); logistics and supplies (p = 0.121); OPV posts (p = .589); and, support system (p = 0.545). Hence, the nurse's performance was not affected at all by the adequacy or inadequacy of these factors. Nurses were able to perform well even with adequate or minimal manpower, logistics and supplies and support system. In the same manner, the adequacy or inadequacy of factors related to KOP activities did not affect KOP coverage outcome.In this study, therefore, KOP outcome cannot be attributed solely to nurse performance as well as adequacy of factors. We can only conclude on the extent of participation of the nurse in KOP activities that: i) during the preparatory phase, the nurse, as planner/organizer in target and logistics-centered activities, was directly involved in carrying out important/initial functions; ii) on the succeeding activities in the preparatory phase (manpower-centered, personnel-centered, community-centered, social mobilization), the nurse' involvement declined because most of the tasks have to be delegated. The nurse, being the coordinator and supervisor, took over areas that seemed to be showing poor results.In order to measure nurse performance vis-a-vis KOP outcome, the Department of Health needs to clarify or delineate the nurse's roles and functions from other health team members making sure that there are no overlap and duplication. This study further revealed the importance of the following components in the success of KOP activities: a) presence of mobile teams; b) scheduling of immunization activities from weekdays to weekendsl; c) strengthening linkage for quality participation of the non-government organizations (NGOs), government organizations (GOs) and other partner agencies.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Community health nursing; Community health nurses; Nurses -- Attitudes